Regional Comprehensive Energy System Planning Considering Construction Cost under Dual Carbon Goals. Issue 1 (1st February 2023) - Wei, Dongni; Che, Bin; Zhang, Zelong; Qi, Caijuan; Dong, Xiaojing
Abstract: Under the dual-carbon goal of carbon peaking and carbon neutrality, from the perspectives of energy supply, coupling, consumption, etc., analyzing the carbon reduction path of the regionally integrated energy system and making an overall plan for it is the key to carbon emission reduction in the power industry, boosting an important starting point for the realization of the "double carbon" goal. To this end, under the constraints of carbon targets, a regional comprehensive energy system planning model considering construction cost is proposed that considers optimal construction timing and demand response. First, regional carbon emission quotas were allocated through the baseline method, and a regional comprehensive energy system planning model was established. Finally, the future challenges faced by the regional low-carbon integrated energy system have been prospected.